Emerging Potential of Exosomes on Adipogenic Differentiation of Mesenchymal Stem Cells - Zhong, Yuxuan; Li, Xiang; Wang, Fanglin; Wang, Shoushuai; Wang, Xiaohong; Tian, Xiaohong; Bai, Shuling; Miao, Di; Fan, Jun (Frontiers in Cell and Developmental Biology, 2021)
The mesenchymal stem cells have multidirectional differentiation potential and can differentiate into adipocytes, osteoblasts, cartilage tissue, muscle cells and so on. The adipogenic differentiation of mesenchymal stem cells is of great significance for the construction of tissue-engineered fat and the treatment of soft tissue defects. Exosomes are nanoscale vesicles secreted by cells and widely exist in body fluids. They are mainly involved in cell communication processes and transferring cargo contents to recipient cells. In addition, exosomes can also promote tissue and organ regeneration. Recent studies have shown that various exosomes can influence the adipogenic differentiation of stem cells. In this review, the effects of exosomes on stem cell differentiation, especially on adipogenic differentiation, will be discussed, and the mechanisms and conclusions will be drawn. The main purpose of studying the role of these exosomes is to understand more comprehensively the influencing factors existing in the process of stem cell differentiation into adipocytes and provide a new idea in adipose tissue engineering research.